Kollokationer som fraseologisk kategori set fra forskellige synsvinker - Braasch, Anna (HERMES - Journal of Language and Communication in Business, 2005)
The delimitation of collocations as a category on its own can be done along different lines. The purpose of this paper is to discuss the deﬁnition and use of the term ’collocation’ from various points of view. Collocations differ from free word combinations on one hand and from idioms on the other, having two characteristic features: a certain degree of meaning compositionality and a certain degree of formal, structural and lexical ﬁxedness. These features appear in several combinations which form the basis of different classiﬁcations. First, criteria and classiﬁcations are discussed; second, the use of the term in lexicographic theory and corpus linguistics is analyzed. The discussion is illustrated by a few examples of lexicographic representation in Danish dictionaries. Finally, an outline of various descriptive approaches with their focus on particular features is presented.